Teachers' Strategies in Cultivating Gratitude Character through Islamic Education and Local Cultural Practices in Primary Schools: A Qualitative Approach - Nur Kholik Afandi; Zurqoni Zurqoni (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
Fostering the character of gratitude in students often becomes trapped in static doctrinal approaches, failing to reach the affective depth necessary for meaningful transformation. This study aims to explore and analyze pedagogical strategies that synergize the values of Islamic education and indigenous wisdom to nurture gratitude in primary school students. The research adopted a phenomenology design. Data collection techniques included interviews, focus group discussions, and observations. Data analysis in this study utilizes Robert K. Yin's systematic protocol, involving 25 Islamic Religious Education (IRE) teachers as key participants to uncover the essence of their lived experiences in internalizing gratitude values. The findings revealed that cultivating a character is implemented through a comprehensive orchestration of strategies, including systematic habituation, behavioral modeling, reflection through muhasabah (self-introspection), and the application of cooperative and experiential learning methods integrated with local cultural values. These findings asserted that instilling a character of gratitude is not merely an individual theological disposition but a socio-pedagogical construction that requires the fusion of Islamic educational values and indigenous wisdom to establish robust habituation practices. The implications of this study underscore the importance of shifting the paradigm from moralistic instruction to a reflective, contextually aligned pedagogy that resonates with students' spiritual values and sociocultural realities. This study makes a significant contribution to the development of more dynamic and applicable character education curriculum models at the primary school level.